Der Freiburger Sprachtest: eine Säule der Sprachaudiometrie im deutschsprachigen Raum = The Freiburg speech intelligibility test : a pillar of speech audiometry in German-speaking countries - Hoth, Sebastian (HNO, 2016)
The Freiburg speech intelligibility test according to DIN 45621 was introduced around 60 years ago. For decades, and still today, the Freiburg test has been a standard whose relevance extends far beyond pure audiometry. It is used primarily to determine the speech perception threshold (based on two-digit numbers) and the ability to discriminate speech at suprathreshold presentation levels (based on monosyllabic nouns). Moreover, it is a measure of the degree of disability, the requirement for and success of technical hearing aids (auxiliaries directives), and the compensation for disability and handicap (Königstein recommendation). In differential audiological diagnostics, the Freiburg test contributes to the distinction between low- and high-frequency hearing loss, as well as to identification of conductive, sensory, neural, and central disorders. Currently, the phonemic and perceptual balance of the monosyllabic test lists is subject to critical discussions. Obvious deficiencies exist for testing speech recognition in noise. In this respect, alternatives such as sentence or rhyme tests in closed-answer inventories are discussed.